A technical note on the preparation and staining of unfixed, undecalcified and unembedded fresh and taphonomically altered human bone with five common stains and dyes - Simona A. Dinu; Iris Sluis; Wilma Duijst; Tristan Krap (International Journal of Legal Medicine, 2026)
Abstract Anthropological and forensic investigations often rely on skeletonized human remains as the only piece of evidence for lifestyle, age and post-mortem interval predictions. Recent studies have demonstrated that histological staining has the potential to extend or improve the knowledge that can be extracted from the microstructure of bone. However, histological staining has only been scarcely applied and investigated on (taphonomically altered) human bones, leading to a lack of available methodology. In this study, protocols for the preparation of bone slides for light microscopy and for staining with Hematoxylin and Eosin, Sirius Red & Fast Green, Toluidine Blue, Masson’s Trichrome and Azocarmine G were adapted for use on undecalcified, unembedded and unfixed human bone. The final methods were applied to fresh, fridge stored and taphonomically altered bones to observe differences between the staining outcomes, as well as what information can be drawn from staining. The successfully stained bone sections revealed information regarding morphology and the collagen content of the bone based on the affinity of the stains to targeted microstructures in the bone or to the collagen molecules respectively. These bone preparation and staining methods are a valuable step towards the adaptation of other stains for human bone, and ultimately towards the development of uniformized histological methods to support forensic-anthropological investigations.